Endoscopic transnasal surgery for cerebrospinal fluid rhinorrhea: pilot study - Zhen-zhong FANG; Ming SONG; Ya-zhuo ZHANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2019)
Objective To summarize clinical experience of endoscopic transnasal surgery for treatment of cerebrospinal fluid (CSF) rhinorrhea. Methods From April 2011 to August 2018, 24 cases of CSF rhinorrhea patients were treated by endoscopic transnasal surgery. There were 11 (45.83%) iatrogenic injuries caused by transcranial microsurgical resection of craniopharyngioma (6 cases), endoscopic transnasal surgery for resection of pituitary adenoma (4 cases), or endoscopic transnasal surgery for optic canal decompression (one case). There were also 10 cases (41.67%) of traumatic and 3 cases (12.50%) of spontaneous CSF rhinorrhea. The leaks were located by preoperative CT, MRI, CT cisternography and MR hydrography. Endoscopic transnasal surgery for CSF rhinorrhea repair was performed. Results A total of 27 leaks were found by endoscopy in 24 cases, including 14 iatrogenic, 10 traumatic and 3 spontaneous. They were repaired by materials such as dissociated mucosal flaps, pedicled mucosal flaps, muscle tissue, fat tissue, fascia lata or artificial dura mater via unilateral or bilateral transethmoid, transnaso-sphenoidal or transnasal prelacrimal recess-pterygoid approaches. The success rate of the first operation was 91.67% (22/24), and the success rate of the second operation was 8.33% (2/24), therefore the total success rate was 100%. Two patients (8.33%) suffered from postoperative meningitis, and were cured by intrathecal injection of antibiotics and lumbar cistern drainage. All patients were followed-up for average 20 months, and no one relapsed. Conclusions Endoscopic transnasal approach is an effective technique for treating CSF rhinorrhea. It has the advantages of accurate location, small trauma, less postoperative complications and so on. Lumbar puncture or lumbar cistern drainage helps to improve the effect of surgery.